Vasopressin and epinephrine versus epinephrine in management of patients with cardiac arrest: a meta-analysis - Jing XL; Wang DP; Li X; Li H; Liao XX; Xiong Y; Wang XF (Database of Abstracts of Reviews of Effects (DARE), 2011)
CRD SUMMARY: This review concluded that there was no evidence that vasopressin and epinephrine was more effective in treating cardiac arrest than epinephrine alone, except for reported 24-hour survival rate in one small study; further research was needed. The methods of the review and quality of included data were unclear and so the conclusions may be unreliable.